QUANTIFYING REAL-TIME RETAIL IMPACT: INFLUENCER MEDIATION IN BOOSTING FASHION INTENTION - Erwin Erwin; Gefael Triady; Francesco Chandra; Krisna Dharmawan Lionary; Jenifer Mariana Wiasal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyse the causal pathway from Live Streaming Commerce to Purchase Intention in the fashion sector, by validating Influencer as a mediating variable. Using an explanatory quantitative approach, this study applied Partial Least Squares – Structural Equation Modelling (PLS-SEM) to survey data collected from 217 fashion consumers in South Sulawesi who have been involved in livestreaming commerce and are affordable to Influencers. The data collection instrument used was a questionnaire with a Likert scale (5 Scales). The main results show that, although livestreaming commerce has a positive and significant direct influence on Purchase Intent, the mediating influence channelled through Influencers is the dominant and superior transmission channel. These findings confirm that for urban consumers who demand authentic product validation, trusted Influencer figures serve as an essential mechanism that transforms real-time interactions into confidence to transact. The implications of this study are significant for fashion industry players, underscoring the need to shift the focus from just technology features to credible influencer authorisation strengthening strategies to achieve optimal conversion rates in a risk-averse regional market.